Clinical Heart Failure Among Patients With and Without Severe Mental Illness and the Association With Long-Term Outcomes. (October 2021) - Polcwiartek, Christoffer; Loewenstein, Daniel; Friedman, Daniel J.; Johansson, Karin G.; Graff, Claus; Sørensen, Peter L.; Nielsen, René E.; Kragholm, Kristian; Torp-Pedersen, Christian; Søgaard, Peter; Jensen, Svend E.; Jackson, Kevin P.; et al.
Abstract : Background: Patients with severe mental illness (SMI) including schizophrenia, bipolar disorder, and severe depression have earlier onset of cardiovascular risk factors, predisposing to worse future heart failure (HF) compared with the general population. We investigated associations between the presence/absence of SMI and long-term HF outcomes. Methods: We identified patients with HF with and without SMI in the Duke University Health System from 2002 to 2017. Using multivariable Cox regression, we examined the primary outcome of all-cause mortality. Secondary outcomes included rates of implantable cardioverter defibrillator use, cardiac resynchronization therapy, left ventricular assist device implantation, and heart transplantation. Results: We included 20 906 patients with HF (SMI, n=898; non-SMI, n=20 008). Patients with SMI presented clinically 7 years earlier than those without SMI. We observed an interaction between SMI and sex on all-cause mortality ( P =0.002). Excess mortality was observed among men with SMI compared with men without SMI (hazard ratio, 1.36 [95% CI, 1.17–1.59]). No association was observed among women with and without SMI (hazard ratio, 0.97 [95% CI, 0.84–1.12]). Rates of implantable cardioverter defibrillator use, cardiac resynchronization therapy, left ventricular assist device implantation, and heart transplantation were similar between patients with and without SMI (6.1% versus 7.9%, P =0.095). Patients with SMI receiving these procedures for HF experienced poorer prognosis than those without SMI (hazard ratio, 2.12 [95% CI, 1.08–4.15]). Conclusions: SMI was associated with adverse HF outcome among men and not women. Despite equal access to procedures for HF between patients with and without SMI, those with SMI experienced excess postprocedural mortality. Our data highlight concurrent sex- and mental health-related disparities in HF prognosis, suggesting that patients with SMI, especially men, merit closer follow-up. Abstract : Supplemental Digital Content is available in the text.